Level, slope, curvature of the sovereign yield curve, and fiscal behaviour - Afonso, António; Martins, Manuel M.F. (Journal of Banking & Finance, 2012)
We study fiscal behaviour and the sovereign yield curve in the US and Germany. We obtain the latent factors, level, slope and curvature, with the Kalman filter, and use them in a VAR with macro, fiscal and financial stress variables. In the US, fiscal shocks generate an immediate response of the short-end of the yield curve, associated with monetary policy, lasting 6–8 quarters, followed by a response of the whole yield curve lasting 3years, with an implied elasticity of long-term yields of 80% for the government debt shock and 48% for the budget balance shock. In Germany, fiscal shocks have entailed no significant reactions of the yield curve shape and no response of the monetary policy interest rate, notably after 1999; only in the case of debt shocks there is a short-lived decrease in the medium-end of the yield curve in the following 2nd and 3rd quarters.